Older worker stereotypes among human resource professional in four Singapore industries - Koh, Cui Shan (2013)
This study focuses on the Human Resources (HR) professionals’ perception on generational differences in work attitudes such as work performance, intent to leave, ability to learn and organizational citizenship behavior.